2010
DOI: 10.3340/jkns.2010.48.4.371
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Neurocysticercosis in Entire Spinal Level

Abstract: J Korean Neurosurg Soc 48 : [371][372][373][374] 2010 Cysticercosis is the most common parasitic infection affecting the central nervous system. Spinal neurocysticercosis (NCC) is very rare compared with intracranial NCC and requires more aggressive management because these lesions are poorly tolerated. The authors report a case of intradural extramedullary cysticercosis of the entire level of spine with review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…[54] Although spinal involvement was considered unusual, a recent study found it in 50 - 70% of patients with basal subarachnoid disease, apparently asymptomatic in most cases (unpublished data, T. Nash & H. Garcia, 2011). The degree of involvement and stage vary from arachnoiditis mostly in the cauda equina, minimal involvement with one or few cysts, to mass effects resulting in paralysis or uncommonly numerous cysts.…”
Section: Symptomatic Diseasementioning
confidence: 99%
“…[54] Although spinal involvement was considered unusual, a recent study found it in 50 - 70% of patients with basal subarachnoid disease, apparently asymptomatic in most cases (unpublished data, T. Nash & H. Garcia, 2011). The degree of involvement and stage vary from arachnoiditis mostly in the cauda equina, minimal involvement with one or few cysts, to mass effects resulting in paralysis or uncommonly numerous cysts.…”
Section: Symptomatic Diseasementioning
confidence: 99%
“…Neurocysticercosis focus in the cranium, is seen in approximately 75% patients (range 30%-100%). 9,10 Isolated spinal involvement of cysticercosis is extremely rare, occurring in less than 25% patients. 5,11 The earliest incidence of spinal cysticercosis was reported in 1963 by Canelas, who noted SCC in 2.7% patients with Neurocysticercosis.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…12 Нe reported incidence of SCC varies from 0.7%-5.85%. 9,10,13,14 Spinal Cysticercosis most commonly involves the thoracic spine and is most commonly associated with a primary inside a spinal cord. A few cases involving the cervical and lumbar cord were also found.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…Most (80%) spinal NCC occurs in the subarachnoid space. [83] The thoracic region is most commonly affected followed by cervical. Intramedullary Cysticercosis (IMC) is far less common with only 53 cases have been reported until 2010.…”
Section: Cysticercimentioning
confidence: 99%